Challenges to the Poultry Industry: Current Perspectives and Strategic Future After the COVID-19 Outbreak - Hafez, Hafez M.; Attia, Youssef A. (Frontiers in Veterinary Science, 2020)
Poultry immunity, health, and production are several factors that challenge the future growth of the poultry industry. Consumer confidence, product quality and safety, types of products, and the emergence and re-emergence of diseases will continue to be major challenges to the current situation and the strategic future of the industry. Foodborne and zoonotic diseases are strictly linked with poultry. Eradication, elimination, and/or control of foodborne and zoonotic pathogens present a major challenge to the poultry industry. In addition, the public health hazards from consuming foods with high antibiotic residues will remain a critical issue. The theory of poultry production described in this review will not be limited to considering disease control. Rather, it will also incorporate the interconnection of the animals’ health, welfare, and immunity. It is essential to know that chickens are not susceptible to intranasal infection by the SARS-CoV-2 (COVID-19) virus. Nevertheless, the COVID-19 pandemic will affect poultry consumption, transport, and the economics of poultry farming. It will also take into consideration economic, ethical, social dimensions, and the sustenance of the accomplishment of high environmental security. Stockholders, veterinarians, farmers, and all the partners of the chain of poultry production need to be more involved in the current situation and the strategic future of the industry to fulfill human demands and ensure sustainable agriculture. Thus, the present review explores these important tasks.